Murals as catalysts for tourism growth in Muar town: public perceptions and future potential - Rong, Yiwei; Hasna, Mohd Fabian (Faculty of Art and Design, 2025)
Muar Town, also known as Bandar Maharani, is a royal city in Johor, Malaysia, strategically located between Singapore and Kuala Lumpur. Known for its historical, cultural, and geographical significance, with the Muar River flowing into the Strait of Malacca, it remains an underutilized tourism destination compared to the nearby UNESCO World Heritage site of Malacca City. In Muar Town, there is a famous mural called "The Loving Sisters," painted by Russian artist Julia Volchkova. Additionally, there is a pedestrian street in Muar called Muar Street Art, which has become a local cultural hub and a therapeutic space for autistic children. The murals are deeply beloved by the public and have become the recommended check-in points for Muar tourism on various travel websites. These factors suggest that murals have a growing potential to boost Muar's tourism industry. Therefore, this study aims to examine the potential of murals in fostering tourism in Muar Town. The objective is to assess public satisfaction with the current murals and interest in future mural developments. This research, using a 5-point Likert Scale with 392 participants, reveals moderate satisfaction with current murals in Muar Town’s tourism, compared to a more positive outlook on future murals. The research emphasizes murals' potential to enhance urban identity, tourism, and community pride, highlighting their role in broader tourism strategies. Murals enhance place-making and cultural expression, offering policymakers and urban developers strategies for urban growth and tourism. Limitations include a sample mainly of non-tourists and a lack of analysis on the economic and social impacts of murals. Future studies should include diverse respondents, such as tourists, and examine murals' direct effects on tourism revenue and community engagement. A broader approach could guide mural initiatives, boosting Muar’s cultural and economic appeal and reinforcing its identity as a vibrant destination.